Analgesic and antiinflammatory activities of the essential oil from Artemisia sieberi Besser (Brazilian Journal of Pharmaceutical Sciences, 2019)
The analgesic activity of Artemisia sieberi oil was assessed by acetic acid-induced writhing test and Eddy’s hot plate method; while the acute anti-inflammatory effect was investigated by inflammatory paw edema test in rats. The administration rout of the essential oil, standard drugs and the vehicle used in all assays was intraperitoneal injection. The 1 and 2.5 mg/kg doses of the studied oil significantly decreased the number of acetic acid-induced writhes in mice. The dose of 1 mg/kg of the oil also exhibited a central analgesic effect as evidenced by a significant increase in reaction time at several time points after 15 min treatment in the hot plate method. In addition, the 1 mg/kg dose of the oil significantly reduced carrageenan induced paw edema in rats at the first hour of the test by 72.7% inhibition and lasted to the third hour of the test by 74.3% inhibition found to be very close to that of the standard drug, diclofenac sodium (50 mg/kg). The major components of the oil were characterized as camphor (31.2%) and 1,8-cineole (20.0%). The results suggest that A. sieberi essential oil has a significant effect against acute inflammation and has central and peripheral anti-nociceptive effects.